Menguraikan Kepemimpinan Administrasi PAUD: Konsep, Gaya, Dan Solusi Problematika - Putri, Yunita Sukma; Muthia, Ayunda; Azzahra, Putri Khalisa; Suhardi (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2024)
This study discusses the concept of administrative leadership in Early Childhood Education (PAUD) with a focus on the role of the principal in managing administration, improving the quality of the institution, and teacher professionalism. The principal as an administrative leader is responsible for fostering all staff and members of the organization, creating a conducive work climate, and managing change effectively. This study also examines various leadership styles applied in PAUD, such as democratic, authoritarian, and transformational styles, as well as solutions that can be applied to overcome challenges in managing institutions. The results of the study indicate that democratic and transformational leadership styles are more effective in encouraging collaboration and innovation, thereby improving the quality of PAUD services. Therefore, strengthening leadership capacity through training and mentoring is an important solution to realizing professional PAUD that is oriented towards child development. These findings are expected to contribute to the development of administrative leadership management in Early Childhood Education institutions.